Peningkatan Hasil Belajar Menggunakan Model Cooperative Learning Tipe Numbered Head Together di Kelas V Sekolah Dasar - Dwiputri, Winda; Farida, Farida (Universitas Negeri Padang, 2023)
The research is based on real situations, namely low learning outcomes because they have never discussed it so that students are lack of motivation, less appreciative of differences. The general research objective is to describe the progress of the final results of learning in integrated thematic teaching implementing the numbered head together category model in grade V of elementary school no. 11 Kurao Pagang, Padang City. This type of classroom action research uses both quantitative and qualitative. The research took place in two cycles, in February 2023. The subjects were teachers as well as students from class V, a total of 23 children. The results of the research are: 1) The lesson plan for cycle I is 82.1% (C), and cycle II is 94.44% (SB). 2) Implementation of learning from the teacher's point of view in cycle I averaged 82.82% (C), cycle II was 93.75% (SB), as well as the student's aspect scores. 3) The final result of learning in cycle I averaged 74.5 (K), and cycle II was 87.6 (B). The decision is that the numbered head-together category model provides progress in learning outcomes of students in integrated thematic in class V SDN 11 Kurao Pagang, Padang City.